2008
DOI: 10.1111/j.1939-1676.2008.0081.x
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous Electrical Cardioversion of Equine Atrial Fibrillation: Patient Factors and Clinical Results in 72 Treatment Episodes

Abstract: Background: Transvenous electrical cardioversion (TVEC) has been developed for treatment of atrial fibrillation (AF) in horses. The relationship among patient variables, treatment response, and outcome in a typical referral population has not been evaluated.Hypothesis: Patient variables such as age, sex, weight, and duration of arrhythmia affect prognosis for response to treatment and the energy level at which cardioversion occurs.Animals: TVEC was applied to 72 episodes of lone AF in 63 client-owned performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 33 publications
6
57
1
4
Order By: Relevance
“…However, treatment frequently is terminated because of cardiac or noncardiac adverse effects or both 9, 10. Transvenous electrical cardioversion (TVEC) is effective in restoring SR in horses without underlying cardiac disease with reported success rates of approximately 90% 11, 12. However, this procedure requires specialized hospital facilities and equipment.…”
mentioning
confidence: 99%
“…However, treatment frequently is terminated because of cardiac or noncardiac adverse effects or both 9, 10. Transvenous electrical cardioversion (TVEC) is effective in restoring SR in horses without underlying cardiac disease with reported success rates of approximately 90% 11, 12. However, this procedure requires specialized hospital facilities and equipment.…”
mentioning
confidence: 99%
“…Although all currently available commercial troponin I assays were designed for human patients, there are numerous reports of their use in horses with cardiac disease. Published studies have found increases in troponin I levels above presumed reference levels in horses with piroplasmosis, atypical myopathy, ruptured aortic jet lesions, structural cardiac disease and neoplasia, as well as after transvenous electrical cardioversion [1,7,[59][60][61][62]. Serum levels of cTnI showed a statistically significant increase after i.v.…”
Section: Use Of Troponin In Horsesmentioning
confidence: 91%
“…To determine measurement repeatability, 13 horses underwent the same protocol without sotalol administration. The TVEC was performed according to procedures described previously . Shocks were administered under general anesthesia using stepwise increases of the delivered energy (150, 200, 250, 300, and 360 J) until cardioversion.…”
Section: Methodsmentioning
confidence: 99%
“…Even at lower levels of exercise intensity, horses in AF might exhibit extremely high heart rates (HRs), and collapse has been described . The success rate for both pharmacological cardioversion and TVEC is very high, but AF recurrence after treatment is common with an overall rate of recurrence up to 39% at 1 year after cardioversion . The pathophysiology of AF initiation and perpetuation in horses has not yet been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%